Pemanfaatan Tepung Ampas Kopi Robusta (Coffea canephora l.) sebagai Substitusi Tepung Terigu dalam Pembuatan Brownies Kukus - Rizky Nirmala Kusumaningtyas; Wildhatul Aluf Fitriatin; Setyo Andi Nugroho; Ujang Setyoko (Jurnal Kridatama Sains dan Teknologi, 2026)
Indonesia is recognized as one of the largest coffee producers in the world, with robusta as one of its leading varieties. Based on data from the Central Statistics Agency (2023), Indonesian coffee exports in 2023 reached USD 915.92 million with a total volume of 276,280.8 tons. The increasing coffee consumption has led to a significant rise in coffee waste, particularly coffee grounds. Several studies have shown that coffee grounds contain high fiber content and possess considerable antioxidant potential. Therefore, coffee grounds have strong potential to be utilized as a substitute ingredient in bakery products, especially in brownies formulation. This study was conducted in October 2024 at the PHP Laboratory of Politeknik Negeri Jember. The research employed an experimental method using a Completely Randomized Design (CRD) with a non-factorial model. The treatments consisted of variations in coffee ground flour substitution levels in brownie formulations. Organoleptic evaluation was conducted based on five parameters, namely taste, aroma, texture, color, and overall acceptance, using a Likert scale (1–5) with 32 panelists. The collected data were analyzed using ANOVA followed by the Honestly Significant Difference (HSD) test at a 5% significance level. The results indicated that treatment O2 showed the highest preference in several parameters, particularly taste (4.38), color (4.06), and overall acceptance (4.03). These findings demonstrate that robusta coffee ground flour substitution significantly affects the organoleptic characteristics of brownies. Therefore, coffee grounds can be considered a potential alternative ingredient for developing value-added bakery products based on food waste utilization